KETAHANAN SOSIAL KOMUNITAS ADAT JALAWASTU TERHADAP PERUBAHAN SOSIAL DI DESA CISEUREUH KABUPATEN BREBES - Hendra Pramudya; Theresia Martina Marwanti; Yana Sundayani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
The Jalawastu Indigenous Community is a community group that still maintains traditional values and traditions, in carrying out daily activities. Social resilience refers to the social unity of individuals, organizations or communities that have aspects of coping capacities, adaptive capacities and transformative capacities with various environmental and social changes. This study aims to determine the resilience of the Jalawastu Indigenous community to social change in Ciseureuh Village, Keanggungan District, Brebes Regency. The method used in this study is a qualitative research method. This research provides a deeper understanding of the social resilience of the Jalawastu Indigenous Community in the face of social change. Data collection techniques used are in-depth interviews, observation, and documentation studies. The results of the study stated that the Jalawastu Indigenous Community still has a fairly good social resilience in responding to social changes. Aspects of coping abilities are marked by still holding high traditional values in deliberation and family solidarity. The aspect of adaptability in responding to social change is carried out while maintaining customary values and accepting social changes that are beneficial to the community. Regarding the aspect of transformational capacity, the Jalawastu Indigenous Community is still in the process of making changes for the better to maximize the available local potential. The Jalawastu Indigenous Community still has good social resilience in facing social changes in Ciseureuh Village, Keanggungan District, Brebes Regency.